Proton pump inhibitor therapy does not increase serum endotoxin activity in patients with cirrhosis. Issue 2 (9th October 2018) - Okura, Yasushi; Namisaki, Tadashi; Sato, Shinya; Moriya, Kei; Akahane, Takemi; Kitade, Mitsuteru; Kawaratani, Hideto; Kaji, Kosuke; Takaya, Hiroaki; Sawada, Yasuhiko; Shimozato, Naotaka; Seki, Kenichiro; et al.
Abstract : Aim: Proton pump inhibitors (PPIs) are frequently prescribed in patients with cirrhosis, but this therapy entails potential complications. We aimed to investigate the influence of PPI use on intestinal permeability in patients with cirrhosis. Methods: We recruited 228 patients with cirrhosis and divided them into four groups. Group (Gp)1 comprised patients receiving a PPI with concurrent neomycin (NEO) (PPI‐NEO group, n = 14 [6.1%]), Gp2 and Gp3 comprised those receiving either PPI or NEO (PPI group, n = 91 [39.9%]; and NEO group, n = 11 [4.4%]), and Gp4 comprised those receiving neither of these medications (control group; n = 112 [49.1%]). We assessed the intestinal permeability by measuring endotoxin activity (EA) using a luminol chemiluminescence method. Results: Endotoxin activity levels were significantly higher in patients with Child B cirrhosis than in those with Child A cirrhosis, but we found no significant differences in EA levels between patients with Child C cirrhosis and those with either Child A or B cirrhosis. We observed no significant differences in EA levels among groups 1–4. Patients without antibiotic exposure ( n = 203), comprising 91 patients on PPI therapy (Gp2) and 112 no‐PPI‐therapy controls (Gp4), were subdivided according to Child–Pugh (CP) classification. We found no significant differences in EA levels between Gp2 and Gp4 in either CP class. Conclusion: Our results suggest that PPI usage does not have a significant impact on serum levels of gut‐derived endotoxins, which are already elevated because of the increased intestinal permeability in patients with cirrhosis.